2010
DOI: 10.1089/vim.2010.0051
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Reproductive and Respiratory Syndrome Virus–Induced Immunosuppression Exacerbates the Inflammatory Response to Porcine Respiratory Coronavirus in Pigs

Abstract: We performed a comprehensive analysis of innate and adaptive immune responses in dual-virus infected pigs to understand whether a pre-existing immunomodulatory respiratory viral infection affects the overall immunity to a subsequent porcine respiratory coronavirus (PRCV) infection in pigs. Pigs were either mock-infected or infected with porcine reproductive and respiratory syndrome virus (PRRSV), a virus known to cause immunosuppressive respiratory disease, and then pigs were co-infected with PRCV, which norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
123
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 47 publications
2
123
0
1
Order By: Relevance
“…Homogenate (wt/vol) (lysate) of a piece of cranial lobe of the lung was prepared in DMEM containing antibiotics, aliquoted and stored at À80 C until used for virus detection (Khatri et al, 2010;Renukaradhya et al, 2010). Briefly, MDCK cells cultured in 96-well tissue culture plates were inoculated with serial 10-fold dilution of the lung homogenate in DMEM and supplemented with TPCK…”
Section: Detection Of Virus Replication In the Lung Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…Homogenate (wt/vol) (lysate) of a piece of cranial lobe of the lung was prepared in DMEM containing antibiotics, aliquoted and stored at À80 C until used for virus detection (Khatri et al, 2010;Renukaradhya et al, 2010). Briefly, MDCK cells cultured in 96-well tissue culture plates were inoculated with serial 10-fold dilution of the lung homogenate in DMEM and supplemented with TPCK…”
Section: Detection Of Virus Replication In the Lung Tissuementioning
confidence: 99%
“…Lung homogenate samples were subjected to cytokine analysis by ELISA (Khatri et al, 2010;Renukaradhya et al, 2010) to detect the levels of innate (IFN-a), proinflammatory (IL-6), Th1 (IFN-g and IL-12), and immunosuppressive [IL-10 and transforming growth factor b (TGF-b)] cytokines. Briefly, ELISA plates were coated with predetermined concentration of cytokine coating antibodies, IFN-a (Thermo Scientific), IFN-g (BD Biosciences), IL-6 and IL-12 (R&D Systems), IL-10 and TGF-b (Invitrogen) and incubated overnight at 4 C. Plates were washed and blocked and the test samples were added along with respective cytokine standards and incubated at RT.…”
Section: Determination Of Cytokine Concentrations In Lung By Elisamentioning
confidence: 99%
See 1 more Smart Citation
“…Lung lysates from all the euthanized pigs were prepared as described previously (3, 36) and frozen at Ϫ20°C until cytokine analysis by enzyme-linked immunosorbent assay (ELISA). Lung lysates were analyzed for innate (IFN-␣), proinflammatory (IL-6), Th2 (IL-4), Th1 (IFN-␥ and IL-12), and anti-inflammatory/T-regulatory (IL-10 and transforming growth factor ␤ [TGF-␤]) cytokines by ELISA as described previously (1,24,36).…”
Section: Virusmentioning
confidence: 99%
“…Previous reports have shown that blood NK cell cytotoxicity is suppressed with no appreciable changes in their frequency in blood after 8 days of PRRSV infected pigs Renukaradhya et al, 2010). Interestingly, we detected IL-15 mRNA level in PBMC at 7, 10, and 14 days after PRRSV-infected pigs (data not shown), finding that IL-15 was slightly up-regulated (about 2 fold) at 7 days after PRRSV-infected pigs, but IL-15 was suppressed at 10 and 14 days after PRRSV-infected pigs.…”
Section: Il-15 Deficient Mice Infected With Vaccinia Virus Cannot Conmentioning
confidence: 89%